2016
DOI: 10.1080/1354750x.2016.1252959
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of 1-hydroxypyrene, 1- and 2-hydroxynaphthalene, 3-hydroxybenzo[a]pyrene and 6-hydroxynitropyrene by HPLC-MS/MS in human urine as exposure biomarkers for environmental and occupational surveys

Abstract: The method is suitable both for occupational and for environmental studies. This is the first paper reporting urinary levels of 6-hydroxynitropyrene in European subjects, nonoccupationally exposed to nitro-PAHs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Simultaneous quantitation of five urinary monohydroxylated metabolites of four polycyclic aromatic hydrocarbons (PAHs) was carried out using an HPLC-MS/MS analytical method: 1-hydroxypyrene (1-OHPy), 1-hydroxynaphthalene (1-OHNAP), 2-hydroxynaphthalene (2-OHNAP), 3-hydroxybenzo[a]pyrene (3-OHBaPy), 6-hydroxynitropyrene (6-OHNPy) [51]. Results were normalized for the creatininuria.…”
Section: Pahs Biomonitoringmentioning
confidence: 99%
“…Simultaneous quantitation of five urinary monohydroxylated metabolites of four polycyclic aromatic hydrocarbons (PAHs) was carried out using an HPLC-MS/MS analytical method: 1-hydroxypyrene (1-OHPy), 1-hydroxynaphthalene (1-OHNAP), 2-hydroxynaphthalene (2-OHNAP), 3-hydroxybenzo[a]pyrene (3-OHBaPy), 6-hydroxynitropyrene (6-OHNPy) [51]. Results were normalized for the creatininuria.…”
Section: Pahs Biomonitoringmentioning
confidence: 99%
“…The use of MS techniques, particularly GC and liquid chromatography (LC), are indispensable tools in metabolomic science owing to their high sensitivity and specificity. Relatively to assessment of B[a]P exposure -the only PAH classified as category 1 by International Agency for Research on Cancerurinary 3-OH-B[a]P determination plays a fundamental role; the hyphenated chromatographic MS procedures proposed for its analysis are based on age-old methodologies resulting in many manual operations with related uncertainty of the determination and higher overall costs of the method [26,27,29,[33][34][35][36]. The use of liquid/liquid extraction (LLE) or SPE with evaporation to dryness of the collect analyte solution followed by reconstitution in a suitable solvent for injection into the chromatographic system -with or o not derivatization -are the typical sequences for monohydroxy PAHs in urine.…”
Section: Resultsmentioning
confidence: 99%
“…Currently four GC methods using N-methyl-N-(trimethylsilyl) trifluoroacetamide (BSTFA) as derivatizing agent previous extraction with hexane or pentane and related analysis by single [27], QpQ [34], or high-resolution [26,35] MS were proposed. Regarding the LC-triple quadrupole analyses, Raponi et al [29] and Zangh et al [36] reported use of SPE, while Luo et al [33] included also the reaction by dansyl chloride (DNS). From the analytical evaluation of the seven above indicated methods we revealed that i) phenolic compounds are susceptible to oxidation with related losses of OH-PAHs and addition of gallic acid (50 µg/mL urine) prior to evaporation and derivatization steps was effective for inhibiting losses (lower than 5%), in according by Jacob et al [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of analytical methods to identify suitable risk-control strategies for occupational hygiene conservation programs have aroused interest in the scientific community. Most analytical methods have been published to measure urinary OH-PAHs [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], which have two to three benzene rings, and only eleven studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] have considered the determination of OH-PAHs with more than three benzene rings, particularly 3-OH-B[a]P.…”
Section: Introductionmentioning
confidence: 99%